Discovery of a human parvovirus B19 analog (Erythroparvovirus) in cats - Lanave, Gianvito; Pellegrini, Francesco; Diakoudi, Georgia; Catella, Cristiana; Cavalli, Alessandra; Capozza, Paolo; Elia, Gabriella; Di Martino, Barbara; Zini, Eric; Pollicino, Giuseppe; Zatelli, Andrea; Bányai, Krisztián; et al. (Scientific reports, 2025)
Two feral cats (from the same colony) were presented to the veterinary clinic for weakness, weight loss, and anorexia. The cats were part of a study on feline hepatotropic viruses (collection A, 43 animals). On metaviromic investigation, parvoviral reads were identified in the sera of the two cats. The feline parvovirus genome was 5.3 kb long with an organization similar to other members of the Erythroparvovirus genus. In the ORF1 (nonstructural proteins) and ORF2 (VP1/VP2 precursor) the feline virus displayed 43.1% and 49.1% nucleotide identity to human parvovirus B19, and 48.9% and 56.6% to chipmunk parvovirus. Sequence identity to canine/feline protoparvovirus (Protoparvovirus carnivoran 1) was as low as 36.5% % and 29.2% in the ORF1 and ORF2, respectively. Using a quantitative PCR assay, the virus was also identified in an additional ten cats (prevalence 27.6%, 12/43) from collection A and in 15/1150 (1.3%) of archival sera (collection B), revealing a higher infection rate in cats with altered hepatic markers, suggestive of hepatic distress. The findings of our study extend the list of known parvoviruses in the feline host.